The Relation of IGF-1 and Insulin Resistance in a Sample of Iraqi Obese Type 2 Diabetic Patients with Macrovascular Disease (Baghdad Science Journal, 2012)
Type 2 diabetes mellitus(T2DM) is a metabolic disease that is associated with an increased risk for atherosclerosis by 2-4 folds than in non- diabetics. In general population, low IGF-1 has been associated with higher prevalence of cardiovascular disease and mortality .This study aims to find out the relationship between IGF-1 level and other biochemical markers such as Homeostasis Model Assessment insulin resistance(HOMAIR) and Body Mass Index(BMI) in type 2 diabetic patients . This study includes (82) patients (40 females and 42 males) with age range (40-75) years,(34) non obese diabetic patients and (48) obese diabetic patients. The non obese individuals considered as a controls group, all controls and patients groups with type 2 DM, ischemic heart disease and hypertension, and free from other disease by history and clinical exam .The results showed that serum IGF-1 levels were lower in obese diabetic patients than non obese.HOMAIR has been found to be significantly higher in obese than non obese diabetic patients ,there is negative correlation between IGF-1 and HOMAIR. Body mass index (BMI) was in positive correlation with HOMAIR and innegativecorrelationwithIGF-1. Conclusion of this study was the serum level of IGF-1 is significantly lower in obese than non obese type 2 DM , but HOMA IR is significantly higher in obese diabetic subjects .